AB0756 Primary efficacy and safety of adalimumab in nail psoriasis from the first 26 weeks of a phase-3, randomized, placebo-controlled trial with subanalysis in patients with and without psoriatic arthritis. (15th June 2017) - Elewski, BE; Rich, PA; Behrens, F; Guillet, G; Geng, Z; Servin, O Reyes
Abstract : Background: Psoriasis (Ps) disease burden for patients (pts) with psoriasis (Ps) and concomitant fingernail Ps plus psoriatic arthritis (PsA) is higher compared with pts with Ps alone. Objectives: We report safety and efficacy of originator adalimumab (ADA) in pts with fingernail Ps, and also for pts with or without concomitant PsA. Methods: Results are reported from the double-blind PBO-controlled, Period A in which 217 pts with moderate to severe plaque Ps and fingernail Ps were included and randomized 1:1 to receive 40 mg ADA every other week (eow) from wk 1 (initial 80 mg dose at wk 0), or matching PBO, for 26 wks. The primary endpoints were the proportion of pts with ≥75% improvement in modified Nail Ps Severity Index (mNAPSI 75) and the proportion of pts with Physician's Global Assessment of Fingernail Psoriasis (PGA-F) of clear (0) or minimal (1) with ≥2-grade reduction from baseline (primary in US only; for regulatory purposes). Missing data were handled by multiple imputation. Safety was assessed using treatment-emergent adverse events (AEs). Results: Of the 217 randomized pts (108 PBO, 109 ADA), 84.3% were male; mean age was 46.7 years; 188 (86.6%) completed 26 wks of treatment or early escaped to Period B according to protocol. Both primary endpoints were met: total fingernail mNAPSI 75 was achieved by 3.4% PBO vs 46.6% ADA (p<0.001), and PGA-F 0 or 1 with ≥2 grades improvement was achieved by 6.9% vs 48.9% (p<0.001). At baseline, 28.6% had PsA (29.6% PBO, 27.5% ADA) with mean duration 7.91 years [SD 8.314]. Total fingernail mNAPSI 75 was achieved by 0.5% PBO vs 61.5% ADA of pts with PsA and 4.6% PBO vs 40.9% ADA without PsA (p<0.001 for both groups). PGA-F 0 or 1 with ≥2-grade reduction was achieved by 4.4% PBO vs 59.3% ADA with PsA and 7.9% PBO vs 44.9% ADA without PsA (p<0.001 for both groups). Adverse events (AEs) in Period A were reported by 55.6% PBO vs 56.9% ADA (with PsA: 56.3% PBO vs 56.7% ADA; without PsA: 55.3% PBO vs 57.0% ADA without PsA); serious AEs by 4.6% PBO vs 7.3% ADA (with PsA: 9.4% PBO vs 10.0% ADA; without PsA: 2.6% PBO vs 6.3% ADA). Conclusions: The primary results demonstrated that in this population, ADA was more effective than PBO for the treatment of fingernail Ps, and significantly improved signs and symptoms, both overall and regardless of the presence or abscense of PsA; no new safety risks were identified with ADA eow treatment for 26 wks. Acknowledgements: AbbVie Inc. funded this study and participated in the study design; study research; collection, analysis and interpretation of data; and writing, reviewing and approving of this publication. All authors had access to the data, and participated in the development, review, and approval, and in the decision to submit this publication. The authors would like to acknowledge Yihua Gu for statistical support, and Jody Bennett, for medical writing support in the production of this abstract; both are employed by AbbVie. Disclosure of Interest: B. E. Elewski Grant/research support from: Abbvie, Amgen, Boehringer Ingelheim, Celgene, Incyte, Lilly, Merck, Novan, Novartis, Pfizer, Valeant, and Viamet, Consultant for: Anacor, Celgene, Lilly, Novartis, Pfizer, and Valeant, P. A. Rich Grant/research support from: AbbVie, Allergan, Amgen, Anacor, Cassiopea, Dusa, Eli Lilly, Galderma, Janssen, Leo, Meiji, Merck, Novartis, Pfizer, Psolar, Ranbaxy, Sandoz, and Viamet, Consultant for: AbbVie, Eli Lilly, Novartis, Sandoz, Polichem and Valeant, F. Behrens Grant/research support from: AbbVie, Amgen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, and Sanofi, Consultant for: Abbvie, Chugai, Celgene, Genzyme, Lilly, Novartis, Pfizer, Roche, and Sanofi, G. Guillet Grant/research support from: AbbVie, Z. Geng Shareholder of: AbbVie, Employee of: AbbVie, O. Reyes Servin Shareholder of: AbbVie, Employee of: AbbVie